The Use of Official Notice in a Refugee Determination Process - Houle, France (Les Cahiers de droit, 1993)
Official notice allows members of administrative tribunals to take into account on their own motion a large scope of information in the decisionmaking process. With this rule of evidence, it is possible to reach a double objective of fairness and expeditiousness. In this article, the author examines the rule of evidence. She also studies the practice of the Convention Refugee Determination Division of taking official notice of « standardized country files ». These files compile information on conditions prevailing in refugee-producing countries. This study is important because the content of these files can be used to determine whether each of the 20 000 and more claimants for refugee status in Canada has a well-founded fear of persecution. The author concludes that standardized country files can be officially noticed as long as the Convention Refugee Determination Division discloses the information in conformity with the rules of natural justice.